Pendekatan Komunikasi Islam dalam Menggali Minat dan Bakat Konseli - Afandi, Rizma Rizwanda (Journal of Islamic Communication Studies, 2025)
This study aims to understand the role of interpersonal communication in exploring students’ interests and talents at the non-formal counseling institution Jari Potensi (JaPo) Surabaya. Many adolescents struggle to recognize their personal potential, which often leads to confusion when determining their academic pathways and career directions. Using a descriptive qualitative approach, this research explores the application of Islamic communication principles in uncovering clients’ interests and talents through counseling services at Jari Potensi, positioning interpersonal communication as the fundamental basis of interaction between counselors and clients. The findings indicate that interpersonal communication characterized by openness, empathy, warmth, and positive regard is effective in creating a comfortable and supportive counseling relationship. The Islamic communication approach is reflected through the principles of ‘qaulan sadīdan’, ‘qaulan layyinan’, and ‘qaulan ma‘rūfan’, which strengthen a dialogical interaction that is polite, reassuring, and free from judgment. The integration of these values not only helps clients understand their interests and talents but also enhances their self-confidence, self-awareness, and motivation to develop their potential. This study emphasizes that interpersonal communication is not merely a tool for exchanging information but a humanistic process that facilitates personal transformation. The findings are expected to serve as a reference for other counseling institutions in developing services grounded in empathetic and reflective communication.